2007
DOI: 10.1007/s12263-007-0051-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of intestinal inflammation and identification of related gene expression changes in mdr1a−/− mice

Abstract: Multidrug resistance targeted mutation (mdr1a -/-) mice spontaneously develop intestinal inflammation. The aim of this study was to further characterize the intestinal inflammation in mdr1a -/-mice. Intestinal samples were collected to measure inflammation and gene expression changes over time. The first signs of inflammation occurred around 16 weeks of age and most mdr1a -/-mice developed inflammation between 16 and 27 weeks of age. The total histological injury score was the highest in the colon. The inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 27 publications
6
81
0
Order By: Relevance
“…In colonic tissue, to our knowledge, there is no report of ABCB4 gene expression in the literature. As in this study, chronic colonic inflammation as observed in IBD patients and in animal models of IBD can result in a down-regulation of other ABC genes, such as ABCB1A and ABCB1B [38][39][40] suggesting a dysregulation of the ABC transporters during inflammation. In contrast, PUFA-enriched diets resulted in an up-regulation of the ABCB4 gene and likely, in a more optimal lipid translocation.…”
Section: Discussionsupporting
confidence: 59%
“…In colonic tissue, to our knowledge, there is no report of ABCB4 gene expression in the literature. As in this study, chronic colonic inflammation as observed in IBD patients and in animal models of IBD can result in a down-regulation of other ABC genes, such as ABCB1A and ABCB1B [38][39][40] suggesting a dysregulation of the ABC transporters during inflammation. In contrast, PUFA-enriched diets resulted in an up-regulation of the ABCB4 gene and likely, in a more optimal lipid translocation.…”
Section: Discussionsupporting
confidence: 59%
“…In 6/16 animals (37.5%) (mice nos. 7,8,15,16,24, and 32), lesions were detected in more than one organ with a maximum score of histologic severity of 11 in mouse no. 16 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is expressed during differentiation of dendritic cells and is constitutively expressed in macrophages (1,12). Until now, ADAMDEC1 has primarily been studied on a transcriptional level, where it has been found differently regulated in a number of pathologies (13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%